Ketangguhan Wilayah Distrik Sorong Timur terhadap Bencana Banjir - Suharyadi Suharyadi; Janviter Manalu; Auldry F. Walukow; Johnson Siallagan; Maklon Warpur (Pusat riset dan Inovasi Nasional, 2025)
Floods are one of the most common natural disasters and have a significant impact on the social, economic, and environmental aspects of society. This is particularly evident in the community of East Sorong District. East Sorong District is one of the areas frequently affected by floods, and this inevitably leads to numerous risks and consequences. There are several causes of flooding in the Sorong Timur District, including extreme rainfall, inadequate drainage systems due to trash blockages, uncontrolled land use changes resulting in overpopulation, and the loss of forest areas or green spaces that could function as water absorption zones. Additionally, the lack of flood control systems and weak oversight of development in flood-prone areas can exacerbate flood disaster risks. This study aims to analyze and measure the resilience of the Sorong Timur District in facing flood disasters through an evaluation approach focusing on infrastructure, service facilities, socio-economic factors, community capacity and preparedness, and institutional aspects. It was concluded that the infrastructure variable is still moderate, while the socio-economic variable, basic capacity, and community preparedness, as well as institutional capacity, are still low. Meanwhile, service facilities are also low. Overall, it can be concluded that the resilience of the Sorong Timur district in facing hydrometeorological disasters is weak.